Penerapan Algoritma Rice Codes dan Algoritma Rivest Shamir Adleman (RSA) Untuk Kompresi dan Pengamanan Teks Pada Aplikasi Chatting - Vify Ernanda; Surya Darma Nasution; Fince Tinus Waruwu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
With the development of information in this day and age chat plays an important role in all aspects of human life. Where chat as a communication tool that can help communicate without any time restrictions and is free from obstacles. But in communicating through chat applications can not be free or as free in communicating as usual. Where chat has a predetermined number of bits, so that in sending text messages the chat application cannot be at once or in one delivery but in multiple transmissions. Therefore the chat application requires a compression where the text messages to be sent through the chat application do not take a long time and do not send several times. It is enough to send only one text message to those addressed. But sometimes text messaging is not only a problem in many or few text messages to be sent there are other obstacles in sending text messages that must be overcome. Text messages that have been sent to those intended, sometimes the text messages have changed not at its disposal or not the same as what was sent. Therefore the chat application is in need of security on the chat application which can secure text messages to be sent to the intended destination without changing one bit. Chat applications provide solutions to communication problems because they are hampered by distance and time. Chat application provides convenience in communicating chat to several people who have great distances by applying the Rice Codes and Rivest Shamir Adleman (RSA) algorithm to chat applications that are designed using Miscrosoft Visual Basic 2008 programming language as a means of compressing and securing text messages.